Psychometric analysis of a simplified version of the Emotion Regulation Questionnaire in Mexican adults: The ERQ-CA-9 - Pablo D. Valencia; Anabel De la Rosa-Gómez (Interacciones)
Background: The Emotion Regulation Questionnaire (ERQ) is the most widely used measure of cognitive reappraisal and expressive suppression, two core emotion regulation strategies. However, the original ERQ has complex wording, which may make it difficult for readers of lower educational levels. Objective: We aimed to examine the psychometric properties of a simplified version of the ERQ, initially designed for children and adolescents: the ERQ-CA. Method: A sample of 397 Mexican adults was studied (77.3% women, 22.7% men; mean age = 22.84). A confirmatory factor analysis, as well as a graded response model, were used to study the internal functioning of the instrument. In addition, its associations with three psychopathological variables (anxiety, depression, and suicidal ideation) were examined. Results: A 9-item version of the ERQ-CA showed adequate fit (CFI = .95, RMSEA = .06), as well as good reliability (ωreappraisal = .76; ωsuppression = .75). Both subscales performed better at levels closer to the mean of their respective constructs. Finally, significant correlations were found between both subscales and the psychopathological variables. Conclusion: The 9-item ERQ-CA constitutes a promising alternative to measure cognitive reappraisal and expressive suppression in the Mexican adult population.